Validation and Refinement of a Prediction Rule to Identify Children at Low Risk for Acute Appendicitis - Kharbanda, Anupam B (2012)
OBJECTIVE: To validate and refine a clinical prediction rule to identify which children with acute abdominal pain are at low risk for appendicitis (Low Risk Appendicitis Rule). DESIGN: Prospective, multi-center cross-sectional study. SETTING: Ten pediatric hospital emergency departments. PARTICIPANTS: Children 3–18 years old who presented with suspected appendicitis from May 2009 – April 2010. MAIN OUTCOME MEASURES: The test performance of the Low Risk Appendicitis Rule. RESULTS: Among 2625 patients enrolled, 1018 (38.8%; 95% confidence interval [CI] 36.9% – 40.7%) had appendicitis. Validation of the rule resulted in a sensitivity of 95.5% (95% CI 93.9 – 96.7%), specificity of 36.3% (33.9 – 38.9%) and negative predictive value (NPV) of 92.7% (90.1 – 94.6%). Theoretical application would have identified 573 (24%) as low risk, misclassifying 42 patients (4.5%; 95% CI 3.4% – 6.1%) with appendicitis. We refined the prediction rule, resulting in a model that identified patients at low risk if: a) absolute neutrophil count (ANC) ≤ 6.75 × 10(3)/µL and no maximal tenderness in right lower quadrant (RLQ) or b) ANC ≤ 6.75 × 10(3)/µL, maximal tenderness in the RLQ but no abdominal pain with walking/jumping or coughing. This refined rule had a sensitivity of 98.1% (97.0 – 98.9%), specificity of 23.7% (21.7 – 25.9%) and NPV of 95.3% (92.3 – 97.0%). CONCLUSIONS: We have validated and refined a simple clinical prediction rule for pediatric appendicitis. For patients identified as low risk, clinicians should consider alternative strategies such as observation or ultrasound, rather than proceed to immediate imaging with CT.